An in situ Bi-decorated BiOBr photocatalyst for synchronously treating multiple antibiotics in water. Issue 3 (21st December 2018) - Cao, Feng; Wang, Jianmin; Wang, Yunan; Zhou, Jun; Li, Song; Qin, Gaowu; Fan, Weiqiang
Abstract : A well-defined Bi/BiOBr flowerlike heterostructure has been fabricated via an in situ solvothermal strategy, and it exhibited excellent photocatalytic activity for synchronously removing multiple antibiotics coexisting in water. Abstract : Currently, there is an urgent demand for developing new materials to remove antibiotics in the water environment, especially for the simultaneous degradation of multiple antibiotics. Here, we fabricated a novel Bi/BiOBr heterostructure via an in situ solvothermal strategy, and it exhibited excellent visible-light-responsive photocatalytic activity for synchronously removing multiple antibiotics coexisting in water. The Bi nanoparticles could extend the light absorption spectra of the sample and further facilitate electron–hole pair separation. The in-depth electron spin resonance (ESR) results confirm that the active species in Bi/BiOBr are holes (h + ) and superoxide radicals (·O2 − ) under irradiation, and it is also proved that Bi could selectively reduce the formation of ·O2 − in the BiOBr matrix. The coexisting system of TC (tetracycline hydrochloride), CIP (ciprofloxacin) and DOX (doxycycline) could be simultaneously photodegraded to approximately 0% within 30 min by the Bi/BiOBr photocatalyst.